Synthesis and thermoluminescence properties of gamma ray irradiated NaCl:Dy3+ phosphor - Bhujbal, P M; Dhoble, S J (Recent Research in Science and Technology, 2012)
The synthesis and thermoluminescence (TL) properties of γ-irradiated NaCl:Dy3+ phosphors are reported in this paper. The NaCl:Dy3+ phosphors of different concentrations of Dy3+ doped in NaCl host are prepared by a wet chemical method. TL of all phosphors has been recorded for different γ-doses. The nature of variations of peak TL intensities is found to be sublinear with γ-irradiation dose and with the concentrations (0.05-0.5 mol%) of added Dy3+ in all the samples. The dose response curve is linear upto 0.6 kGy. Minimum fading is observed in the prepared sample.